Incidence of Respiratory Distress in Term Newborns Presenting within 72 Hours after Birth at Kalasin Hospital: อุบัติการณ์เกิดภาวะหายใจลำบากภายใน 72 ชั่วโมงแรกหลังเกิดในทารกแรกเกิดครบกำหนดที่คลอดในโรงพยาบาลกาฬสินธุ์ - Dolchalermyuttana, Parichart (Srinagarind Medical Journal, 2024)
Background and Objective: Respiratory distress (RD) is one of the most common problems in term newborns who were admitted to special care newborn unit at Kalasin Hospital and it is the main cause of neonatal morbidity and mortality. This study was conducted to find out the incidence, causes, signs and symptoms, type of oxygen administration and maternal history in term newborns with RD within 72 hours after birth at Kalasin Hospital. Methods: Retrospective descriptive study was conducted during 1st October 2022 to 30th September 2023. Data were reviewed from medical records of 155 term newborns. Data were analyzed using descriptive statistics and analytic statistics. Results: Incidence of RD was 8.8%. Most of them developed RD within 6 hours after birth (86.5%). Transient tachypnea of the newborn (TTNB) was the most common cause (41.9%) followed by congenital pneumonia (25.8%) and early onset neonatal sepsis (EOS) (19.4%). In terms of signs and symptoms 87.5% had tachypnea, 83.9% had retraction and 13.5% had nasal flaring. Suprasternal retraction statistically significantly increased the outcome of newborns with oxygen saturation (SpO2) < 95% (OR 7.27, p = 0.01). They were given respiratory support which included oxygen head box 63.2%, heated humidified high flow nasal cannula (HHHFNC) 29.7% and invasive respiratory support 3.2%. Most common maternal history is gestational diabetes (GDM) (14.9%), followed by meconium-stained amniotic fluid (MSAF) (16.1%) and pregnancy induced hypertension (PIH) (6.5%). Conclusion: RD is a common problem in term newborns. TTNB is the most common cause. Additionally, congenital pneumoniae and early onset neonatal sepsis are also common causes. Symptoms often occur within 6 hours after birth. Therefore, surveillance of RD during this period is crucial for prompt diagnosis and appropriate treatment.